A leggyakoribb tulajdon elleni szabálysértések gyakorlati problémái, különös tekintettel a lopásra és csalásra - Kálmánczi, Antal (Debreceni Jogi Műhely, 2016)
In this study, based on the procedure of the Central Summary Offences in Hajdú-Bihar, I will try to present the most common practical problems of summary offence against property (particulary theft and fraud), First of all, my article describes the legal background as to why summary offence procedure is called „petty criminal law” in Hungary, and as a result what legal basis are being used for criminal concepts. In the second part of the study I will present some resolution to the most common and the most important legal imperfections and problems. Last but not least I will make an attempt to disclose the most common issues, which might occur in the so-called „quick procedure”, the „bring to court”. In summary I hope, my study can be of useful assistance to the summary offence procedure and can elevate standard/level of the procedure.